Permeability of work-life balance on Lecturers turnover intentions in Ghana: a multicentre study - Mensah, Grace; Alexander Akumbuno,; Joy Seko Abra Amankwa,; Elliot Akuna,; Francis Owusu-Sekyere,; Bernard Kissi-Abrokwah, (Technium Social Sciences Journal, 2026)
The permeability of work-life balance (WLB) is causing employee turnover, affecting personal and professional lives. The study aims to investigate the impact of WLB on lecturers’ turnover intentions in Ghana. The study was underpinned by WLB theory and job embeddedness theory. An interpretive paradigm using an exploratory design with semi-structured interviews was adopted to seek the views of 16 participants on the permeability of WLB and lecturers’ turnover intentions in Ghana. The participants in the study were lecturers from public universities in Ghana. It was revealed that the factors contributing to WLB among lecturers were a heavy workload and long working hours, stress caused by work, inadequate institutional support, the utilisation of technology and connectivity, a lack of boundaries, and expectations and demands from institutions, on the issue of how WLB influences lecturers' turnover intentions. It was reported that it impacts individual well-being and the inability to pursue personal interests outside of work. However, the study also revealed strategies and interventions to mitigate WLB and promote job satisfaction among lecturers based on training and professional development, implementing flexible work arrangements, establishing realistic job demands and clear workload expectations, work-life policies and guidelines, and collaboration and teamwork.